Pemanfaatan Facebook Sebagai Media Promosi Bisnis Dalam Usaha Meningkatkan Jumlah Penjualan Bagi Ibu-Ibu PKK Kelurahan Bangunsari Kecamatan Dolopo Kabupaten Madiun - Ferlin Kurniawati; Maulida Nurhidayati (IAI Darussalam, 2021)
With the rapid development of information, so that humans no longer care about the problems of space and time. One example is the internet, now the internet has a role as the main source of information where the network is available throughout the hemisphere. In the process of getting information, the internet involves not only one or two people, but up to thousands to millions of people who are in all parts of the world. From here arises interaction between human beings, until the formation of a social networking site. In social networks, humans can not only exchange information, but can also exchange photos and videos, and can even be used as one of the media to do business online. One example, the most popular social network is Facebook, which is used as a marketing medium. Marketing is one of the important elements in running a business. The production turnover of a product can be said to be successful if the marketing system it runs is good. Marketing not only develops products optimally, sets attractive prices, and provides goods for consumers, but must be able to communicate well with consumers. The obstacle that is often faced is to reduce the cost of communication media to do marketing. Today, the world of marketing is heavily influenced by the internet, even the internet is used as an attractive and profitable means of marketing. Facebook Marketing is one of the marketing media that is online which is through internet intermediary media with various facilities available in the Facebook social network.